Informacja Bieżąca . no. 7, 1981 - Uniwersytet Warszawski NSZZ "Solidarność" Region Mazowsze, [ed. Teresa Butrym, Andrzej Walewski] (NSZZ "Solidarność" UW, 1981)
Creation and circulation: For internal use